Stimulation of narration: from Examining Preconceptions to Education - Martin Klimovič (Ignatianum University Press, 2019)
Meaningful development of productive text competence in pupils of primaryschool age should be based on a detailed analysis of their intuitive conceptualisation of particular text models (narration, description, explication,argumentation), their characteristics and the method of creating text. In this paper we, therefore, focus on an analysis of 8-year-old children and their preconceptions of narration. The findings from the interviews with this group of 8 year-old children are presented in relation to the capacity of a particular pupil to create a narrative text. Utilising the intervention program Self-Regulated Strategy Development (Harris & Graham), we point out the pitfalls in developing the narrative competence of children. In doing so, it is essential to take into consideration the pupil's conceptual, procedural, and metacognitive knowledge of text production.